Herding behavior in dividend policy: case study of Malaysia - Nurul Nadiah, Rusle (2013)
The purpose of this study is to prove the existence of the herding behavior in dividend policy and the tendencies of one company to follow others in the same industry in Malaysia. Consistent with previous research, this paper explores imitative influence on dividend policy in Malaysia. It will prove whether there is herding behavior in the dividend policy or not. The result shows that the imitative influence, herding behavior or intra-industry conformity in dividend policy exist in Malaysia. More than 80 percent of the responded companies in trade and services industry are paying dividend to their shareholder. This result also indicates that there is similarity in dividend payout among firms in the same industry. Overall, the results are consistent with imitation in dividend policy. This study documents the relevance of social imitation mechanism behind dividend payout behavior and therefore it will adds to the current knowledge of the existence of herding behavior in Malaysia